RETRACTED: Mitochondrial tRNA Mutations Associated With Essential Hypertension: From Molecular Genetics to Function - Liu, Yuqi; Chen, Yundai (Frontiers in Cell and Developmental Biology, 2021)
Essential hypertension (EH) is one of the most common cardiovascular diseases worldwide, entailing a high level of morbidity. EH is a multifactorial disease influenced by both genetic and environmental factors, including mitochondrial DNA (mtDNA) genotype. Previous studies identified mtDNA mutations that are associated with maternally inherited hypertension, including tRNAIle m.4263 A>G, m.4291T >C, m.4295 A>G, tRNAMet m.4435 A>G, tRNAAla m.5655 A>G, and tRNAMet/tRNAGln m.4401 A>G, et al. These mtDNA mutations alter tRNA structure, thereby leading to metabolic disorders. Metabolic defects associated with mitochondrial tRNAs affect protein synthesis, cause oxidative phosphorylation defects, reduce ATP synthesis, and increase production of reactive oxygen species. In this review we discuss known mutations of tRNA genes encoded by mtDNA and the potential mechanisms by which these mutations may contribute to hypertension.